Simulative Study of Black Hole Attack for Wireless Networks and Network Performance Analysis Over NS2 - Jain, Monika; Saxena, Rahul; Kumar, Aashis; Sadana, Tushar; Jain, Vidyanshu; Jaidka, Siddharth (International Journal of Engineering and Technology, 2018)
Wireless networks are the most popular and widely used class of networks in the world. Because of its extreme level usage, it is more prompt to attack in the network. In recent times there has been increase in the frequency of cyber-attacks for example Ransomware that has affected various organization of different sectors (Health care, defense etc). In order to prevent such attacks on our systems it is important to understand the methodology of these attacks and how they impact the efficiency of available network.Â  This paper provides us the insight about how such an attack is performed and what are the counter measure we can take to improve the security of network system in place around the world. The major objective of the paper is the simulation of Black hole attack on a wireless network and studying its effects. We have also evaluated the network efficiency with varying number of nodes under the conditions of with and without attack.Â Â
Keywords: Security; efficiency; black hole attack